An Investigation of the Physical Mechanisms of Orbital Period Variations of the Semidetached Binary UW Vir - Jia Zhang (2018)
The orbital period variations of the Algol-type semidetached binary UW Vir are analyzed. It is shown that in addition to a long-term rapid increase (dP/dt = + 1.37 × 10-6day/year), its orbit period has a variation with the period of 62.3 years. Based on the basic physical parameters given by Brancewicz and Dworak in 1980, the physical mechanisms causing the orbital period variations are investigated. The analysis indicates that the periodical variation of orbital period can be interpreted by the light-travel time effect due to the presence of a third body with the mass of M3≥ 0.94 Mȯ. As no observational information has been reported for this tertiary component, it might be a compact object (e.g., a white dwarf). The long-term increase of orbital period can be explained in terms of the mass transfer from the secondary to the primary component (dM2/dt = 1.43 × 10-7Mȯ/year). This is in agreement with the semidetached configuration of the system with a lobe-filling secondary component. But according to the evolution theory of binaries, the Algol-type semidetached binary UW Vir should be at the evolutionary stage of slow mass transfer on the nuclear-reaction timescale of the secondary component. However, the analysis shows that the timescale for the periodical variation of orbital period is much shorter than the nuclear-reaction timescale of the secondary component, but close to the thermodynamic timescale of the secondary. This reveals that: (1) This binary system is at the evolutionary stage of rapid mass transfer on the thermodynamic timescale of the secondary component; or (2) The circumstellar matter of the system makes a contribution to the rapid increase of orbital period via the angular momentum transfer. © 2009.